2016
DOI: 10.1073/pnas.1614057113
|View full text |Cite
|
Sign up to set email alerts
|

Generation of an inducible colon-specific Cre enzyme mouse line for colon cancer research

Abstract: Current mouse models for colorectal cancer often differ significantly from human colon cancer, being largely restricted to the small intestine. Here, we aim to develop a colon-specific inducible mouse model that can faithfully recapitulate human colon cancer initiation and progression. Carbonic anhydrase I (Car1) is a gene expressed uniquely in colonic epithelial cells. We generated a colon-specific inducible Car1 CreER knock-in (KI) mouse with broad Cre activity in epithelial cells of the proximal colon and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 42 publications
(43 reference statements)
1
39
0
Order By: Relevance
“… 6 , 30 An excellent study using a carbonic anhydrase Cre recombinase to target colonic enterocytes showed that Apc loss and Kras activation, but not Apc loss alone, can drive tumour growth in differentiated cells and generate ‘top-down’ tumours. 31 Apart from these studies, very little is known about the pathways that confer plasticity in adult intestinal epithelium. Here, we show that loss of the TGF β signalling pathway induces the formation of more aggressive tumours, which are mainly responsible for the significant reduction of the overall survival.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 30 An excellent study using a carbonic anhydrase Cre recombinase to target colonic enterocytes showed that Apc loss and Kras activation, but not Apc loss alone, can drive tumour growth in differentiated cells and generate ‘top-down’ tumours. 31 Apart from these studies, very little is known about the pathways that confer plasticity in adult intestinal epithelium. Here, we show that loss of the TGF β signalling pathway induces the formation of more aggressive tumours, which are mainly responsible for the significant reduction of the overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…These transgenic and knock-in alleles including Fabp-Cre [51], Cdx2-Cre [52], Cdx2-CreER [53], CAC [54], and Car1-CreER [55], all enable reproducible, colon-restricted gene inactivation or activation, depending on the genetic context. One recent publication describes the development of the Car1-CreER strain, which outlines an extremely complex model to generate oncogenic mutations in the four most common CRC-associated alterations ( Apc, Kras, Trp53 and Smad4 ) [55]. This is an impressive example of what can be accomplished with traditional genetically engineered mouse models (GEMMs), but also a cautionary tale.…”
Section: Models Of Colon Biology and Crcmentioning
confidence: 99%
“…The majority of data on stem cells in the mammalian digestive tract are derived from studying the mouse SI; however, a major caveat to using mice to investigate intestinal physiology relevant to human beings is species-specific differences in regional biology. 2 It is imperative that we use reliable in vitro models to study human gut stem cell behavior because human in vivo analyses generally are impractical. Three-dimensional organoids, self-organizing cultures of ISCs, and their progeny have transformed our ability to study human intestinal physiology and stem cell function.…”
mentioning
confidence: 99%